Implementasi Building Information Modeling (BIM) 5D Pada Pekerjaan Struktur Rumah Tinggal Type 400: Studi Kasus di Perumahan Grand City - Muhammad Ardin; Irna Hendriyani; Reno Pratiwi (Institut Teknologi Garut, 2025)
Building Information Modeling (BIM) represents a technological advancement in the modern era that continues to develop, particularly in the construction industry, by supporting planning and capital management. One of the software applications that can be used to support BIM is Autodesk Revit. The objective of this research is to compare the results of cost estimation for building structures using conventional methods and BIM, applied to a type 400 residential house project located in Balikpapan, East Kalimantan Province, within the Grand City housing area. The study focuses on calculating structural work costs, highlighting significant differences in structural components, particularly in reinforcement and concreting work. The findings indicate a cost difference of 16.82% in reinforcement work and 12.7% in concreting work, resulting in an overall budget estimation discrepancy of 15.62%. Based on these results, this study concludes that the use of BIM is highly necessary for identifying and evaluating cost estimation in building or construction planning from the perspective of project planners.